The coupling between peripheral microcirculation and slow breathing. (January 2017) - Ovadia-Blechman, Zehava; Gavish, Benjamin; Levy-Aharoni, Danit; Shashar, David; Aharonson, Vered
Highlights: Breathing temporally couples to capillary flow at low skin oxygenation levels. This coupling gradually increases as breathing rate slows down. Capillary flow response to skin oxygenation change is potentiated at low oxygenation. Abstract: Vasomotion (rhythmic changes in arteriolar diameter) is believed to enhance tissue perfusion at low oxygenation levels. We hypothesized that slow breathing and vasomotion may correlate temporally ("coupling"), especially at low oxygenation levels. We paced down spontaneous breathing to about 5 or 6 breaths/min in 14 healthy subjects using device-guided breathing (DGB), and continuously monitored respiration, transcutaneous oxygen pressure ("oxygenation"), and skin capillary blood flow ("microflow") using a laser Doppler flowmeter. The coupling was expressed by cross-correlation calculated in 1-min time windows. Our main results illustrated that: (1) coupling increased gradually upon slowing breathing down in a subgroup, in which initial oxygenation was lower than a threshold of 30 mmHg (0.3 ± 0.2 vs. 0.07 ± 0.2, P  < 10 −6 ); (2) during DGB changes in oxygenation elicited opposite (relative) changes in microflow, with 4-fold higher sensitivity for low initial oxygenation relative to high (regression slope −0.094 ± 0.010 mmHg −1 vs. −0.020 ± 0.002 mmHg −1, P  < 10 −6 ); (3) at low initial oxygenation, we observed larger coupling and (relative) microflow changes in younger subjects, and greater oxygenation changes in females ( P  < 10 −6 for all); (4) pulse pressure changes from before to after DGB were reduced by increased oxygenation changes during DGB (−5.5 ± 7.4 mmHg, r  = −0.73, P  < 0.001). In conclusion, the present methodology can provide the variation trend of respiration–vasomotion coupling during DGB that may characterize microcirculation behavior at tissue oxygenation below a measurable threshold. The potential association of these trends and thresholds with pathologies or specific conditions of the cardiopulmonary system, and the possible role played by the neural sympathetic activity in that coupling, deserve further studies.